Health characteristics of reproductive-aged autistic women in Ontario: A population-based, cross-sectional study. (May 2021) - Tint, Ami; Brown, Hilary K; Chen, Simon; Lai, Meng-Chuan; Tarasoff, Lesley A; Vigod, Simone N; Parish, Susan; Havercamp, Susan M; Lunsky, Yona
While an increasing number of girls and women are being identified with autism, we know little about the health of reproductive-aged autistic women. Our objectives were to (1) describe health characteristics of reproductive-aged autistic women who could potentially become pregnant and (2) compare these characteristics with those of non-autistic women. We conducted a population-based cross-sectional study using 2017–2018 administrative health data from Ontario, Canada. A total of 6, 870 fifteen- to 44-year-old autistic women were identified and compared with 2, 686, 160 non-autistic women. Variables of interest included social determinants of health (neighborhood income, residential instability, material deprivation, rurality), health (co-occurring medical and psychiatric conditions, use of potentially teratogenic medications, history of assault), and health care factors (continuity of primary care). Overall, reproductive-aged autistic women had poorer health compared with non-autistic women, including increased rates of material deprivation, chronic medical conditions, psychiatric conditions, use of potentially teratogenic medications, and history of assault. These findings highlight the need for health interventions tailored to the needs of reproductive-aged autistic women. Lay abstract: While an increasing number of girls and women are being identified with autism, we know little about reproductive-aged autistic women's health. This study used administrative data from Ontario, Canada, to compare the health of reproductive-aged autistic women with non-autistic women. Overall, reproductive-aged autistic women had poorer health compared with non-autistic women, including increased rates of material deprivation, chronic medical conditions, psychiatric conditions, history of assault, and use of potentially teratogenic medications (i.e. drugs that can be harmful to the development of an embryo or fetus). These findings suggest that there is a need for health interventions tailored to the needs of reproductive-aged autistic women.